FORECASTING FINTECH STOCK INDEX DURING COVID-19 OUTBREAK - Budi Setiawan; Muhammad Yunus (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2022)
The health crisis caused by the coronavirus (Covid-19) is becoming increasingly severe. Policies such as curfew and lockdowns have impacted decreasing the spread of the virus but pose challenges for the global economy and financial markets. This study investigates the effect of Covid-19 pandemic on the Fintech stock index during the health pandemic. This paper uses the new Covid-19 index dataset, consisting of medical index, travel index, uncertainty index, Covid index, vaccine index, and aggregate Covid index. The KBW NASDAQ financial technology index (KFTX) is adopted as a proxy of the Fintech stock index. Several methods, namely MLRA, PCRA, and Lasso, are applied in predicting factors affecting the Fintech stock index. The findings reveal that PCRA is more efficient and simple in predicting Fintech stock index than MLRA and Lasso. This study also finds that vaccine index positively impacts, while the other five variables, such as aggregate Covid index, medical index, travel index, uncertainty index, and Covid index have a negative correlation to Fintech stock index. Despite the fact that Covid-19 is still evolving, the findings provide the determinants of the Fintech stock index that will be useful for investors to diversify their portfolio of financial assets during a crisis.